(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2020)
The purpose of the research: Promote the strengthening of critical thinking in early childhood education students, Cúcuta expansion. The type of research was participatory action research, the population consisted of 33 subjects including students and teachers. The results obtained were able to identify gaps in the educational system and possible changes from the requirement of the first semesters. In this way, improve planning as a pedagogical strategy where the integral formation of the educator in training prevails